Weight Gain, Lifestyle, and Cognition During the COVID-19 Pandemic in Southern Brazil. Issue 2 (June 2023) - Vargas, Liziane da Silva de; Jantsch, Jeferson; Varela, Ana Paula Muterle; Dorneles, Gilson Pires; Zanini, Roberta de Vargas; Peres, Alessandra; Guedes, Renata Padilha
Background: During the COVID-19 pandemic, the world experienced social distancing that resulted in changes in habits and lifestyle. Such changes can compromise healthy eating habits and the practice of physical activities, known risk factors for developing weight gain and obesity. Objective: The main objective of this study was to describe the change in eating habits, lifestyle, and cognition of the population of Rio Grande do Sul, a state in Southern Brazil, during social distancing due to COVID-19. Methods: The study was conducted from July 21 to August 10, 2020, through a structured online questionnaire that asked for sociodemographic information (age, gender, and education), anthropometric (reported weight and height), change in eating habits, lifestyle (sleep quality and physical activity), and cognition. Chi-square, McNemar tests, and univariate and multivariate analysis were used to evaluate the variables. Confidence intervals were calculated with a significance level of 5%. Results: Of a total of 1072 participants, 57.3% of respondents reported weight gain, and an increased percentage of people were classified as obese. Nearly half of the participants (46%) reported changes in their eating habits for the worse. Body mass index (BMI) was significantly associated with increased consumption of unhealthy foods. Our results identified high physical inactivity (46.9%) and obesity (19%) during social distancing. The changes in eating habits and lifestyle also increased the risk for decreased cognition. Conclusions: These findings highlighted that social distancing impacted eating habits and lifestyle, which increased obesity rates and might predispose to decreased cognition.